Parental acceptability of newborn screening expansion in the genomic era: A nationwide French survey informed by the Theoretical Framework of Acceptability (SeDeN-p3) - Camille Level; Laurence Faivre; Margot Lemaitre; Dominique Salvi; Isabelle Marchetti-Waternaux; Elisabeth Cudry; Emmanuel Simon; Nicolas Bourgon; Alexandra Benachi; Nhut-Thanh Van; Camille Coppola; Christine Binquet; et al. (PLoS ONE, 2026)
Background Newborn screening (NBS) has progressively expanded through technological innovations, from tandem mass spectrometry enabling expanded NBS (eNBS) to the prospect of genomic NBS (gNBS). While these developments promise earlier diagnosis and richer information, they also raise concerns regarding actionability, uncertainty, equity and psychosocial impact. As technological feasibility alone does not ensure public confidence, parental perspectives are central to evaluating future expansions. This study assessed parental views on NBS expansion in France, examining its determinants and whether genomics raises specific concerns. Methods A nationwide cross-sectional survey (September 2022–February 2023) included 1,640 parents recruited postpartum in maternity wards and through an online quota panel. Acceptability of eNBS and gNBS was assessed alongside intermediate components from the Theoretical Framework of Acceptability (affective attitude, perceived effectiveness, ethicality), a technical trade-off scenario, and individual characteristics. Analyses combined descriptive statistics, multivariable regression, and thematic analysis of free-text comments. Results Support was very high for eNBS (93%) and remained high for gNBS (89%), with genetics mainly shifting responses from complete to partial acceptability. Affective attitude and perceived effectiveness were the strongest predictors of both outcomes, while ethical concerns distinguished assured from conditional support. Most parents prioritised minimising uncertain results, whereas a smaller subgroup accepted greater ambiguity. Foreign-born and single parents reported lower levels of complete acceptability, while health-sector workers and parents with rare-disease experience were more supportive. No independent association with the age of the youngest child was observed. Conclusion Parental acceptability of eNBS and gNBS is high but nuanced, shaped primarily by anticipated health benefits, emotional orientation and tolerance for uncertainty, with trust and social distance modulating support. As genomic expansion progresses, implementation will require proportionate, culturally adapted information and clear governance, and should be informed by real-world evidence from pilots such as PERIGENOMED.